Finite Element Analysis of Different Pin Diameter of External Fixator in Treating Tibia Fracture - Ramlee, Muhammad Hanif; Zainudin, Nur Amalina; Abdul Kadir, Mohammed Rafiq (International Journal of Integrated Engineering, 2021)
Biomechanical perspective of external fixator is one of the biggest elements that should be considered in treating fracture bone. This is due to the mechanical behavior of the structure could be analyzed and optimized in order to avoid failure, increase bone fracture healing rate and prevents preterm screw loosening. There are three significant factors that affect the stability of external fixator and those are the placement of pin at the bone, configuration and components of external fixator. All these factors contribute to a question, what is the optimum pin diameter which exerts good stress distribution? To date, the research on the above-mentioned factors are limited in the literature. Therefore, this study was conducted to evaluate the unilateral external fixator with different pin sizes in treating tibia shaft fracture via the finite element method. First and foremost, the development of the tibia shaft fracture was conducted using Mimics software. The computed tomography (CT) data image was utilized to develop three-dimensional tibia bone followed by crafting fracture on the bone. Meanwhile, the unilateral external fixator was developed using SolidWorks software. In this study, five pin diameters (4.5, 5.0, 5.5, 6.0 and 6.5 mm) were developed and analyzed. Both tibia bone and external fixator were meshed in 3-matic software. Simulation of this configuration took place in a finite element software, Marc.Mentat. From the findings, it is shown that the larger diameter of pin demonstrated the lowest stress distribution. The size of the 5.5mm pin shows optimum diameter in terms of stress distribution with the value of 21.50 MPa in bone and 143.33 MPa in fixator. Meanwhile the displacement value of 1.42mm in bone and 1.20mm in fixator. In conclusion, it is suggested that the pin diameter of 5.5 mm is the most favorable option in treating tibia shaft fracture in terms of mechanical perspective.